The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1002/ps.3600
|View full text |Cite
|
Sign up to set email alerts
|

Resistance and behavioural response of Plutella xylostella (Lepidoptera: Plutellidae) populations to Bacillus thuringiensis formulations

Abstract: Broad and indiscriminate use of Bt-based products has selected Brazilian P. xylostella populations to resistance. Larval movement appears to be a resistance-independent mechanism. Most populations of P. xylostella preferred to lay eggs on Bt-free surfaces, which might be a result of growers' practice of spraying the cabbage head. Reduced oviposition on treated surfaces correlated with physiological resistance, suggesting a behavioural response among the Bt-resistant colonies to Dipel®WP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 40 publications
1
27
0
2
Order By: Relevance
“…DBM has developed resistance against many different chemical classes of insecticides, such as organophosphates, pyrethroids, benzoylureas, abamectin, indoxacarb and B. thuringiensis ( Bt ) . However, most recently DBM has evolved high levels of resistance against diamide insecticides such as chlorantraniliprole and flubendiamide owing to the extensive use of this new class in different geographies .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DBM has developed resistance against many different chemical classes of insecticides, such as organophosphates, pyrethroids, benzoylureas, abamectin, indoxacarb and B. thuringiensis ( Bt ) . However, most recently DBM has evolved high levels of resistance against diamide insecticides such as chlorantraniliprole and flubendiamide owing to the extensive use of this new class in different geographies .…”
Section: Discussionmentioning
confidence: 99%
“…DBM has developed resistance against many different chemical classes of insecticides, such as organophosphates, pyrethroids, benzoylureas, abamectin, indoxacarb 22,23 and B. thuringiensis (Bt). 24 However, most recently DBM has evolved high levels of resistance against diamide insecticides such as chlorantraniliprole and flubendiamide owing to the extensive use of this new class in different geographies. 11,17,18,25 Here, we have investigated the cross-resistance profile of the diamide-resistant DBM strain Sudlon recently collected in the Philippines 18 and an OP-resistant strain from Japan in comparison with an insecticide-susceptible reference strain (BCS-S).…”
Section: Discussionmentioning
confidence: 99%
“…Although Bacillus thuringiensis (Bt) has proven to be effective against pests belonging to the orders Lepidoptera, Coleoptera and Diptera, the ability of insects to develop resistance to Bt-based products and Cry proteins from Bt has been reported in several species of Lepidoptera, including P. xylostella (Zago et al 2014). For example, populations of P. xylostella resistant to Bt have been reported worldwide (Tabashnik et al 1994;Wright et al 1997;D ıaz-Gomez et al 2000;Gong et al 2010), including Bt-transgenic brassicas (Zhao et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Most research on behavioural resistance has been conducted with Bt‐susceptible larvae (Zhang et al ; Yang et al ; Lu et al ), and only a few experiments have been carried out with larvae that are physiologically resistant to Bt toxin, e.g. for diamondback moth, P. xylostella (Schwartz et al ; Zago et al ), and no studies of this type could be found for H. armigera . Luong et al () found that some H. armigera larvae might not feed on Bt‐treated diet, which raises the question: Can larvae detect Bt and alter their behaviour to avoid it by not feeding?…”
Section: Introductionmentioning
confidence: 99%